Metformin Regulates the Expression of SK2 and SK3 in the Atria of Rats With Type 2 Diabetes Mellitus Through the NOX4/p38MAPK Signaling Pathway. Issue 5 (November 2018) - Liu, Changhe; Hua, Na; Fu, Xi; Pan, Yilong; Li, Bin; Li, Xiaodong
Abstract : Abstract: We previously found that metformin regulates the ion current conducted by the small conductance calcium-activated potassium channels (SK channels) in the atria of rats with type 2 diabetes mellitus (T2DM) as well as the mRNA and protein expression of the SK2 and SK3 subtypes of SK channels. In this study, we hypothesized that the nicotinamide adenine dinucleotide phosphate oxidase 4 (NOX4)/p38 mitogen-activated protein kinase (p38MAPK) signaling pathway was involved in the metformin-mediated regulation of SK2 and SK3 expression in the atria of rats with T2DM. We randomly divided Wistar rats into the control group, the untreated T2DM group, the metformin-treated group, the group receiving subcutaneous injections of the nicotinamide adenine dinucleotide phosphate oxidase (NOX) inhibitor diphenyleneiodonium (DPI), and the group receiving tail vein injections of the p38MAPK agonist anisomycin. Real-time polymerase chain reaction, Western blot, and immunohistochemistry were applied to examine the expression levels of SK2, SK3, NOX4, and phospho-p38MAPK (p-p38MAPK) mRNAs and proteins in the atrial tissue of relevant groups. We observed that the expression levels of NOX4 mRNA and protein and p-p38MAPK protein were significantly elevated in the atria of rats with T2DM compared with the control group. In addition, SK2 protein expression was reduced, whereas SK3 protein expression was increased. The 8-week treatment with metformin markedly reduced the expression levels of NOX4 mRNA and protein and p-p38MAPK protein, upregulated the SK2 expression, and downregulated the SK3 expression. Tail vein injection with anisomycin significantly increased the p-p38MAPK expression while further inhibiting the expression of SK2 and enhancing the expression of SK3. Subcutaneous injection with DPI considerably inhibited the expression of NOX4, further enhanced the expression of SK2 and suppressed the expression of SK3. In addition, subcutaneous injection with DPI significantly suppressed the phosphorylation of p38MAPK. In conclusion, the NOX4/p38MAPK signaling pathway mediates the downregulation of SK2 and the upregulation of SK3 in the atria of rats with T2DM. Long-term metformin treatment upregulates SK2 protein expression and downregulates SK3 protein expression by inhibiting the NOX4/p38MAPK signaling pathway.